2014
DOI: 10.12659/msm.889776
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Trail Making Test and interval timing as measures of cognition in healthy adults: Comparisons by age, education, and gender

Abstract: BackgroundHuman cognitive functioning can be assessed using different methods of testing. Age, level of education, and gender may influence the results of cognitive tests.Material/MethodsThe well-known Trail Making Test (TMT), which is often used to measure the frontal lobe function, and the experimental test of Interval Timing (IT) were compared. The methods used in IT included reproduction of auditory and visual stimuli, with the subsequent production of the time intervals of 1-, 2-, 5-, and 7-seconds durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 28 publications
0
9
1
Order By: Relevance
“…Our study showed no differences between both genders in SCWT3, TMTA and B, but we also found that DTI for males was greater than female RA, which could be due to the fact that males had slightly faster dual and single task speed (STS) compared to females. When comparing TMT values by gender, age and educational level, it was shown that gender and age have an essential role on TMT which reflects processing speed and overlapping cognitive tasks, results showed that females outperform males 48) which was not the case in our findings. The authors speculate this may be due to the sedentary nature of the female population compared to male population recruited within the UAE.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Our study showed no differences between both genders in SCWT3, TMTA and B, but we also found that DTI for males was greater than female RA, which could be due to the fact that males had slightly faster dual and single task speed (STS) compared to females. When comparing TMT values by gender, age and educational level, it was shown that gender and age have an essential role on TMT which reflects processing speed and overlapping cognitive tasks, results showed that females outperform males 48) which was not the case in our findings. The authors speculate this may be due to the sedentary nature of the female population compared to male population recruited within the UAE.…”
Section: Discussioncontrasting
confidence: 79%
“…A longitudinal study conducted in India showed that early life education level plays a role in cognitive differences between females and males 49) However, another study showed that tasks used to measure WM did not find any gender differences in developing sample from young children to older adult population 50) . Considering age groups, a study found that the older the subjects the longer it took them to perform the test 48) . Our results also showed that age groups (18)(19)(20)(21)(22)(23)(24) completed both tests TMTA-B and SCWT3 the fastest.…”
Section: Discussionmentioning
confidence: 99%
“…What is clear from the present study, however, is the lack of relationship between age, education, MMSE, IQ, and visual search based RT performance. This may indicate that such tests are less susceptible to, i.e., relatively independent of, the influence of age, education, and IQ upon performance [ 57, 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most TMT variants are designed in such a way that pulls for such proximity errors (Lezak et al, 2012 ). Research has shown that normal control subjects can make at least one error on both parts of the TMT (Ruffolo et al, 2000 ; Lezak et al, 2012 ) In fact, several factors such as age (Płotek et al, 2014 ) or educational level (Płotek et al, 2014 ) and even shift work history (Titova et al, 2016 ) can affect performance. However, an increased number of errors, especially on TMT-B, has been associated with dorsolateral frontal lobe lesions (Kopp et al, 2015 ) and this finding has been consistent even when compared to subjects with inferior medial frontal lobe and posterior lobe lesions, who made fewer errors or were completely unaffected (Stuss et al, 2001 ; Lezak et al, 2012 ).…”
Section: Trail Making Test (Tmt)mentioning
confidence: 99%